PENGALAMAN TENAGA KESEHATAN DALAM PENCEGAHAN INFEKSI NOSOKOMIAL MYCOBACTERIUM TUBERCULOSIS - Luter Kristian Zai; Imelda Liana Ritonga (Jurnal Ilmiah Keperawatan IMELDA, 2025)
Nosocomial infection of Mycobacterium tuberculosis is a serious challenge in hospitals due to the high risk of transmission to healthcare workers due to direct exposure to tuberculosis patients. This study aims to explore the experiences of healthcare workers in preventing nosocomial Mycobacterium tuberculosis infections at Imelda Buruh Indonesia General Hospital, Medan. This study used a descriptive qualitative research type with a phenomenological approach, involving six participants selected through a purposive sampling technique. Data were collected through in-depth interviews and analyzed using the Colaizzi method. The results revealed four themes, namely: healthcare workers' understanding of nosocomial Mycobacterium tuberculosis, healthcare workers' experiences in preventing nosocomial Mycobacterium tuberculosis infections, challenges faced by healthcare workers in preventing nosocomial Mycobacterium tuberculosis infections, healthcare workers' suggestions for improving policies for preventing nosocomial Mycobacterium tuberculosis infections. The conclusion of this study is that healthcare workers have understood how tuberculosis is transmitted and implemented preventive measures such as the use of masks and patient education. However, limited isolation room facilities, lack of standard personal protective equipment, and low patient and family compliance with protocols are significant obstacles